Challenges and Opportunities in Implementing Intellectual Property Rights Protection System for Creative Industry Development in Indonesia - Judijanto, Loso; A., Chevy Herli Sumerli; Firmansyah, Firmansyah; Solapari, Nuryati; Raihana, Raihana (West Science Law and Human Rights, 2024)
The Indonesian creative industry stands at the intersection of cultural richness, technological advancements, and economic potential. This research undertakes a quantitative analysis to unravel the challenges and opportunities in implementing an Intellectual Property Rights (IPR) protection system for creative industry development in Indonesia. The study involves 100 respondents representing diverse segments of the creative industry. Findings reveal a nuanced landscape, with varying perceptions of the current IPR protection system, significant concerns about challenges such as piracy, and optimistic views on growth opportunities through digital platforms, collaborations, and global markets. Recommendations from creative professionals emphasize the need for legal reforms, increased awareness campaigns, and collaborative efforts. This research contributes valuable insights to inform policymakers, industry practitioners, and stakeholders in fostering a robust and dynamic creative industry in Indonesia.